Morphometric characterization and genetic distance in bitches (oryctolagus cuniculus) in several regions in Indonesia - Auliani Arafah; Abdul Razak; Ramadhan Sumarmin (Tropical Genetics, 2022)
Rabbits are a group of animals that are very popular and enjoyed by the community. Rabbits, in general, have the high biological and economic potential to produce quality meat, skin, and hair, as well as pets (ornamental) and modern business farming. Rabbits are well known in Indonesia and developed mostly for farming. This literature study discusses morphometric characteristics and genetic distances among rabbits. The parameters used were head length (PK), head width (LK), ear length (PTL), ear width (LTL), chest circumference (LKD), chest width (LD), humerus bone length (PH), radius-ulna bone length (PRU), tibial bone length (PT), and body length (PB). The results of body variables measurement in FG rabbits had a higher mean for body size, including PK (12.64 cm), PTL (13.59 cm), LTL (6.47 cm), PH (9.52 cm), PRU (8, 95 cm), and PB (41.97 cm) compared to other families. Genetic distance shows that it has a close genetic distance (0.63106), while the farthest genetic distance is found between Rexb rabbits and ES rabbits, which is 6.96749. The genetic distances and tree phenogram construction are useful for estimating kinship between Rabbits clumps.